Super food: eggs / Wan Noorli Razali - Razali, Wan Noorli (Academy of Language Studies, 2023)
Eggs are a prevalent dietary item across various cultures globally and are frequently included in breakfast menus, baked goods, and several other culinary preparations. They are an outstanding source of protein and a diverse range of vital nutrients, which makes them a highly beneficial inclusion in any diet. Eggs are a rich source of high-quality protein, containing all the essential vitamins A, B2, B6, B12, D, E, and K as well as minerals like iron, zinc, and selenium. These nutrients play essential roles in maintaining good health, building strong muscles, increasing energy production, and preventing chronic disease. The protein in eggs helps weight loss as it keeps the stomach feeling full longer.. Previously, there was a debate on whether eggs were beneficial or harmful for health, mainly due to their cholesterol content. However, the prevailing viewpoint nowadays is that consuming eggs in moderate amounts can be beneficial for health as studies reveal that eggs contain choline, which has a significant role in breaking down homocysteine, an amino acid that could potentially contribute to the development of heart disease. Thus, there is no concrete evidence that links egg consumption to increase in bad cholesterol.